Analisis Kesalahan Penggunaan Ejaan Bahasa Indonesia (EBI) pada Surat Kabar Pergeseran Media Arus Utama dan Meluasnya Ruang Media Baru - Maulana Abdurrasyid (Lembaga Pengembangan Kinerja Dosen, 2024)
his study aims to analyze language errors according to the General Guidelines for Indonesian Spelling (PUEBI) in newspapers amidst the shift in mainstream media to new media. Using a qualitative descriptive approach, this study examines the forms of language errors, such as the use of spelling, punctuation, and sentence structure in newspaper news. The shift in media consumption from print to digital also affects the quality of language presentation. This study found that although digital media facilitates access, language standards are often neglected. This article provides an impression for media development to maintain language quality in facing changes in the digital era.